Potential avenues for exercise to activate episodic memory‐related pathways: a narrative review. (1st August 2017) - Loprinzi, Paul D.; Edwards, Meghan K.; Frith, Emily
Abstract: Memory function plays an important role in activities of daily living, and consequently, quality and quantity of life. In this narrative review, we discuss the anatomical components of episodic memory, including the structure of the hippocampus and the routes of communication to and from this structure. We also highlight cellular traces of memory, such as the engram cell and pathway. To provide etiological insight, the biological mechanisms of episodic memory are discussed, including factors subserving memory encoding (e.g., cognitive attention, neuroelectrical indices), consolidation (i.e., synaptic and brain systems level), and retrieval (e.g., availability of cues, context‐dependent, state‐dependent, and cognitive processing). Central to this manuscript, we highlight how exercise may influence each of these aforementioned parameters (e.g., exercise‐induced hippocampal growth, synaptic plasticity, and cue retrieval) and then discuss the implications of these findings to enhance and preserve memory function. Collectively, this narrative review briefly summarizes potential mechanisms of episodic memory, and how exercise may activate these mechanistic pathways. Abstract : This study highlights potential mechanisms of episodic memory. We highlight how exercise behavior may activate these mechanistic pathways.